Perlindungan Hukum Terhadap Asisten Rumah Tangga (ART) yang Mengalami Kekerasan Ditinjau dari Hukum Ketenagakerjaan - Astri Maharani; Sartika Puspa Sekar Arum; Yusuf Taufiqurahman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The existence of household assistants (ART) is often ignored in labor laws in many countries, including Indonesia. This results in unfair treatment and minimal access for household members to legal protection, which increases the risk of violence against them. This violence includes verbal, physical and sexual harassment, but is difficult for household members to report due to limited legal knowledge and fear of retaliation. Social stigma and lack of support also exacerbate the situation, leaving many cases of violence unreported and perpetrators unaccounted for. This research aims to increase awareness of the importance of legal protection for household members, evaluate the implementation of labor laws, and encourage regulatory changes to expand protection. The research method uses a qualitative and descriptive approach through literature study. The research results show that legal protection for household members in Indonesia is still weak and ineffective, especially because household members are not explicitly regulated in labor law. Key barriers include a lack of rights awareness, training of law enforcement officers, and a culture of amicable resolution of violence. Better legal protection for household members needs to be implemented immediately through the ratification of the Domestic Workers Protection Bill, educational campaigns and training for law enforcement officers. Strong family, community and political support is also needed to create a safer and fairer environment for ART.